Answer:
The factorization of given expression
is (x + 9i)(x – 9i) and option d is correct.
Solution:
Given, expression is
![x^2 + 81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mttqmf94npb1798jk0m8ddnsah9tqsc4j2.png)
We have to factor it in the complex numbers.
Let us check options to find answer.
A) (x – 9)(x – 9)
(x – 9)( x – 9)
![=(x-9)^(2)=x^(2)-18 x+81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lyj4lufcw4t97suikff9csd81j1v7nw20p.png)
So, this is not correct answer.
B) (x + 9)(x + 9)
![(x+9)(x+9)=(x+9)^(2)=x^(2)+18 x+81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8gmhj1qqu7hqavpyeuobvk1ofs89caqlc6.png)
So, this is not correct answer.
C) (x + 9i)(x + 9i)
![(x+9 i)(x+9 i)=(x+9 i)^(2)=x^(2)+18 x i+81(-1)=x^(2)+18 x i-81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q65k85ponsovibben9qcsth3yq43vgdl5o.png)
So, this is not correct answer.
D) (x + 9i)(x - 9i)
![(x+9 i)(x-9 i)=x^(2)-(9 i)^(2)=x^(2)-(-81)=x^(2)+81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tfmpbyc7hzr2beah6fezgwo0v4t3lw5pxj.png)
Thus option D is correct
Hence, the factorization of given expression is (x + 9i)(x – 9i). and option d is correct.